The Influence of Work-Life Balance on Job Satisfaction, Organizational Commitment, and Turnover Intention - Detson Ray Halomoan Sitorus; Kusdi Raharjo; Andriani Kusumawati (Wacana Journal of Social and Humanity Studies, 2018)
This research aims to examine the influence of work-life balance on the employees’ job satisfaction, organizational commitment, and turnover intention in the banking industry. There's a total of 142 questionnaires collected from branch offices and 13 BRI unit offices in Malang. The demographic features were briefly discussed in terms of frequency and percentage. For the analysis of data, descriptive and inferential statistics have been used. Structural equation modeling (SEM) has been used for inferential statistics to measure the degree between independent variables and the dependent variables. The results of this study clearly demonstrate that work-life balance, job satisfaction, and organizational commitment have a negative impact on the turnover intention. Work-life balance, job satisfaction, and organizational commitment have an important relationship in minimizing the turnover intention among the employees in the organization.